Calcium ion biorecovery from industrial wastewater by Bacillus amyloliquefaciens DMS6. (July 2022) - Li, Dan; Zhao, Hui; Li, Guijiang; Yan, Huaxiao; Han, Zuozhen; Chi, Xiangqun; Meng, Long; Wang, Jihan; Xu, Yudong; Tucker, Maurice E.
Abstract: Calcium ions in industrial wastewater needs to be removed to prevent the production of limescale, which can have negative consequences. Biomineralization has become the focus due to its lower costs than traditional methods of remediation. In this study, calcium ions were bio-precipitated under the action of free and immobilized Bacillus amyloliquefaciens DMS6 bacteria, and the calcium ion removal efficiency was also compared. The results show that it only needed 3 days to decrease the calcium ion concentration to an ideal level of 76-116 mg/L under the action of DMS6 bacteria immobilized by activated carbon fiber, with calcium ion removal ratios reaching 99%-95% by the 7 th day. DMS6 bacteria immobilized by activated carbon fiber were superior to free bacteria and bacteria immobilized by sodium alginate in calcium ion removal. Calcium ions are biomineralized into calcite, Mg-rich calcite, aragonite and monohydrocalcite with abundant organic functional groups, 4 types of secondary protein structures, amino acids, phospholipids, negative stable carbon isotope δ 13 CPDB values (-16.68‰ to-17.25‰) and negatively charged biomineral surface. Calcium ions were diffused into cells and took part in the intracellular biomineralization of monohydrocalcite, also facilitating calcium ion removal. The formation of intracellular monohydrocalcite has rarely been reported. This study demonstrates an economic and environmentally friendly method to remove calcium ions from industrial wastewater. Graphical abstract: Image 1 Highlights: DMS6 bacteria immobilized by ACF decreased 99-95% of soluable Ca 2+ on the 7 th day. DMS6 bacteria immobilized by SA decreased 95%-92% of soluable Ca 2+ on the 10 th day. Free DMS6 bacteria decreased 82-81% of soluable Ca 2+ on the 17 th day. The formation of intracellular monohydracalcite also facilitated to Ca 2+ removal. The biogenesis of these calcium carbonate minerals was confirmed.